2014
DOI: 10.1161/circulationaha.113.001696
|View full text |Cite
|
Sign up to set email alerts
|

Visible Age-Related Signs and Risk of Ischemic Heart Disease in the General Population

Abstract: Background-Cardiovascular disease is 1 of the most common age-related diseases, and also 1 of the most common causes of death in the general population. We tested the hypothesis that visible age-related signs associate with risk of ischemic heart disease (IHD), myocardial infarction (MI), and death in the general population, independent of chronological age. Methods and Results-10,885 individuals aged 20 to 93 years free of IHD were followed from 1976 through 1978 until June 2011 with 100% complete follow-up. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 47 publications
(45 reference statements)
3
66
2
2
Order By: Relevance
“…Thus, some investigators have defined ELC severity according to its length and depth, 13 whereas considered only complete ELC, regardless of its inclination or bilateralism, 14 and a recent publication evaluated the right pinna exclusively, thus ignoring bilateralism, and the sample photograph presented to nurses for classification showed a vertical rather than a diagonal ELC. 8 Our detailed analysis of each characteristic has revealed that diagonal bilateral ELC is the most reliable marker of CVEs, agreeing with previous evidences 6 that showed poorer outcomes for cardiologic patients with bilateral ELC compared with those displaying unilateral ELC. The vertical crease has, for the first time, demonstrated a lack of association with CVE.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, some investigators have defined ELC severity according to its length and depth, 13 whereas considered only complete ELC, regardless of its inclination or bilateralism, 14 and a recent publication evaluated the right pinna exclusively, thus ignoring bilateralism, and the sample photograph presented to nurses for classification showed a vertical rather than a diagonal ELC. 8 Our detailed analysis of each characteristic has revealed that diagonal bilateral ELC is the most reliable marker of CVEs, agreeing with previous evidences 6 that showed poorer outcomes for cardiologic patients with bilateral ELC compared with those displaying unilateral ELC. The vertical crease has, for the first time, demonstrated a lack of association with CVE.…”
Section: Discussionsupporting
confidence: 91%
“…The largest prospective study to date (over 10 000 participants) showed that people over 40 years of age with earlobe crease are at risk of vascular disease due to atherosclerosis. 5 In our patient, microcytic anemia was diagnosed. A computed tomography scan of the chest and abdomen revealed continuous extension of thoracic aneurysm and endoleak within the lower part of the stent graft (FIGURE 1B).…”
mentioning
confidence: 59%
“…Tybjaerg-Hansen and others studied over 10,000 Danes and found that ear lobe creases indicated the body's biological age, and was an indicator for heart disease. [11] Studies on Shar Pei dogs suggests that these animals have mucinosis -high hyaluronic acid levels are found in both cutaneous tissues and the blood stream --and these high amounts are due to an excess in the activity (overexpression) of the HAS2 enzyme. [12] Such research avenues are promising as they can shed more light on processes such as cell recognition and ageing.…”
Section: Discussionmentioning
confidence: 99%